MECHANISMS OF ACCOUNTING THE INFORMAL SECTOR IN ECONOMIC DEVELOPMENT - Mavlyanov Muzaffar (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
this article provides information on informal sector accounting and their working mechanisms in foreign countries.